2020
DOI: 10.32539/sjm.v3i1.116
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Kepatuhan Berobat Pasien Kanker Payudara yang Menjalani Kemoterapi di RSUP Dr. Mohammad Hoesin Palembang

Abstract: Kanker payudara berdampak pada 2,1 juta wanita setiap tahun dan menjadi penyebab kematian terbesar kanker pada wanita di dunia. Terapi untuk kanker payudara salah satunya dengan kemoterapi. Dibutuhkan kepatuhan dalam menjalani pengobatan untuk menghindari progresivitas dan kekambuhan penyakit. Jenis penelitian ini adalah deskriptif observasional dengan teknik consecutive sampling. Sampel penelitian ini adalah pasien kanker payudara yang menjalani kemoterapi di RSUP Dr. Mohammad Hoesin pada bulan September 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In 2018, WHO revealed that an estimated 9.6 million people worldwide died of cancer. In the same year, the International Agency for Research on Cancer (IARC) announced that there were 18.1 million new cancer cases and 9.6 million cancer deaths worldwide (Abdulah, 2022). In 2020 it accounted for nearly 10 million deaths, of which one in six deaths was caused by cancer and one of them was lung cancer (Buana & Harahap, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, WHO revealed that an estimated 9.6 million people worldwide died of cancer. In the same year, the International Agency for Research on Cancer (IARC) announced that there were 18.1 million new cancer cases and 9.6 million cancer deaths worldwide (Abdulah, 2022). In 2020 it accounted for nearly 10 million deaths, of which one in six deaths was caused by cancer and one of them was lung cancer (Buana & Harahap, 2022).…”
Section: Introductionmentioning
confidence: 99%